THE DIURNAL PERIODICITY OF AURORA WITHIN THE MAXIMUM-FREQUENCY ZONE - Isaev,S. I. (1960)
Three types of auroral diurnal variations are defined. The first and most simple type, having a single night maximum, is observed in the outer zone, that is, up to about 70 degrees of geomagnetic latitude. The second and more complicated type, exhibiting a secondary morning maximum, prevails in the region between 70 and 78 degrees of geomagnetic latitude, that is, in the transitional zone of magnetic disturbance. The third type, with an unstable or indeterminate diurnal variation, is observed beyond 78 degrees of geomagnetic latitude, that is, in the inner zone of magnetic disturbance. The boundaries between these zones, it seems, do not run strictly according to geomagnetic latitude but have a somewhat oval form. Trans. of Problemy Arktiki (USSR) 1940, no. 9, p. 41-45.